Alteraciones psicológicas asociadas a los cambios en la apariencia física en pacientes oncológicos - Fernández, Ana Isabel (Psicooncología, 2004)
Changes in physical appearance often appear as a consequence of cancer or their treatments and are another stress source that cancer patients must face. Their ability to accept and adapt to these changes has an immediate effect on their emotional state, quality of life, personal, familiar, social and labour performance. This article analyses the variables that have an influence in development of psychological disturbance associated to changes in cancer patients body image. It also shows the most frequently applied psychological interventions. Preventive interventions including emotional support and counselling are advisable to improve patients resistance’s to this undesirable changes. Cognitive-behavioural techniques have been also shown to be effective in this area.